Industrial discrimination on account of HIV and AIDS: perspectives on Botswana and South Africa - Gaedupe, Makgato Lengoko (Centre for Law and Society, 2026)
It is accepted that HIV positive employees or those perceived to be living with the virus encounter various forms of discrimination both in the workplace and in their day to day activities. Therefore, it is incumbent upon the states to come up with prohibitive measures to curb such unwarranted discrimination. The central question of this thesis is an evaluation of the frameworks adopted in Botswana and South Africa. Using a comparative approach it is the finding of this study that Botswana has in place an admirable policy framework whose shortcoming is lack of a legislative back-up. It has also been shown that Botswana's policies enjoy a lot of political support, an attribute that her South African counterpart lacks, Further, it has been shown that South Africa has both legislative and policy framework to protect people living with HIV in the workplace. Finally, it is argued that an ideal framework should boast of both policy and legislative framework which is backed by political will.